An Environmental Education and Communication Project on Migratory Fishes and Fishing Communities - Sara Costa Carvalho; Heitor Oliveira Braga; Sofia de Santa-Maria; Beatriz Fonte; Mário Jorge Pereira; Antonio García-Vinuesa; Ulisses Miranda Azeiteiro (MDPI AG, 2021)
This study aims at evaluating the environmental education (EE) and communication intervention for the valorization of migratory fish resources in an estuary of northern Portugal. The EE component intervention was implemented among Middle School pupils of that region. Students' knowledge was quantitatively evaluated with an experimental approach of pre-testing and post-testing, on the ocean and estuarine literacy (OEL) and biology of migratory species, such as sea lamprey. This study also analyzes the communication component developed via social media. Results of the EE component show an evident increment of OEL (p < 0.05). It is also highlighted that students had previous knowledge on issues that are not covered in the curriculum. Social media has shown to be an effective communication tool mostly among the scientific community (e.g., Ethnobiology). The research has various implications to OEL since it brings a new perspective towards the integration of ocean literacy in formal education; as well as the valorization of Students' local ecological knowledge and of inter-generational dynamics. This study contributed to promoting local biodiversity, OEL, and participatory local governance of these ecosystems.